Intrapartum endotracheal intubation in a fetus with diaphragmatic hernia. A propos of the first ex-utero intrapartum treatment (EXIT) in Peru - Ventura Laveriano, Walter (2016)
We report the case of a pregnant woman attended at our unit with 39 weeks of gestation carrying a fetus affected with left diaphragmatic hernia. An EXIT (ex-utero intrapartum treatment) procedure was carried out in order to reduce hypoxia and aerophagia commonly observed during neonatal intubation. We demonstrate the feasibility of this highly specialized procedure in our local setting, not only for diaphragmatic hernia but also for diseases affecting fetal airway. This procedure is currently a standard procedure in perinatal care of fetuses with diaphragmatic hernia at our hospital.